Excavations in Western Thebes, 2021: The Discovery of the Golden Lost City, A Preliminary Report - Hawass, Zahi.
In 2021, working from the outer wall of Medinet Habu north about 100 meters, west of the road that leads to the Valley of the Queens, and east to the temples of Thutmose III, Ramesses IV and Amunhotep Son of Hapu, the Egyptian Expedition discovered three districts of a city with well-preserved architecture. The borders of the districts have serpentine walls. The artifacts from the main district indicated the manufacture of faience and stone jewelry industry, textiles, and leatherwork. The second shows grinding of grain, baking, and processing meat. Sealings and jar labels show that the name of the city was THn Itn, “The Dazzling Aten” and so it was part of the support city for Malkata and perhaps Amunhotep’s memorial temple. A cemetery dated to Dynasties 25–27 (yet to be fully investigated), was found to the west of the city.